Предмет: Алгебра, автор: InfinityRed

(1-2ab/a^2+b^2):a^2-b^2/a^2+b^2

Ответы

Автор ответа: АннаАрт
0
frac{1-2ab}{a^2+b^2}:frac{a^2-b^2}{a^2+b^2}=frac{1-2ab}{a^2+b^2}*frac{a^2+b^2}{a^2-b^2}=frac{1-2ab}{a^2-b^2}\------------------\
(1-frac{2ab}{a^2+b^2}):frac{a^2-b^2}{a^2+b^2}=(1-frac{2ab}{a^2+b^2})*frac{a^2+b^2}{a^2-b^2}=frac{a^2-2ab+b^2}{a^2+b^2}*frac{a^2+b^2}{a^2-b^2}=\\
=frac{a^2-2ab+b^2}{a^2-b^2}=frac{(a-b)^2}{(a-b)(a+b)}=frac{a-b}{a+b}
Похожие вопросы
Предмет: История, автор: valentina300686v